Effects of the frame geometry on the weight and inelastic behaviour of eccentrically braced chevron steel frames - Ozhendekci, D.; Ozhendekci, N. (ELSEVIER SCI LTD, 2008)
Many experimental and analytical studies about eccentrically braced frames (EBFs) have been carried out since the late 1970s. However, parametric studies about the effects of the frame geometry on the weight and global inelastic behaviour are still quite limited. Such kind of parametric studies require many number of designed EBFs for the purpose of generalization, in fact, optimization of design is also necessary for the conservatism of results. Therefore, a computer program based on an iterative optimization procedure is coded for the design of eccentrically braced chevron frames and the algorithm is given. In this research, 420 EBFs with shear yielding links, 105 EBFs with intermediate links, and 105 EBFs with flexural yielding links are designed. Inelastic dynamic analyses of each of these frames are performed under 20 SAC ground motions with DRAIN-2DX whose input files are prepared automatically by another program coded. Each earthquake record for each frame is scaled by the program by modifying the DRAIN input files in an automated manner until one of the links reaches the code-based limit rotation angle, and the resultant scale factors are utilized for comparison of the frames' inelastic behaviours. The equation for plastic link rotation of EBFs given in AISC-2005, which does not consider the vertical displacements of the column ends is modified to include these displacements and used in the inelastic analyses. Effects of the geometry selection on the frames' seismic behaviours and weights are given, Push-over analyses of some of the designed frames are also performed with DRAIN-2DX in order to compare their displacement ductilities. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: eccentrically braced frame; link length; shear yielding link; flexural yielding link; intermediate link; capacity-based design; inelastic time history analysis; pushover analysis; frame weight; LINK BEAMS; CAPACITY; Construction & Building Technology; Engineering